The genetic architecture of membranous nephropathy and its potential to improve non-invasive diagnosis - ARIKAN, İZZET HAKKI; KOÇ, MEHMET (NATURE PUBLISHING GROUP, 2020)
Membranous Nephropathy (MN) is a rare autoimmune cause of kidney failure. Here we report a genome-wide association study (GWAS) for primary MN in 3,782 cases and 9,038 controls of East Asian and European ancestries. We discover two previously unreported loci, NFKB1 (rs230540, OR = 1.25, P = 3.4 x 10(-12)) and IRF4 (rs9405192, OR = 1.29, P = 1.4 x 10(-14)), fine-map the PLA2R1 locus (rs17831251, OR = 2.25, P = 4.7 x 10(-103)) and report ancestry-specific effects of three classical HLA alleles: DRB1*1501 in East Asians (OR = 3.81, P = 2.0 x 10(-49)), DQA1*0501 in Europeans (OR = 2.88, P = 5.7 x 10(-93)), and DRB1*0301 in both ethnicities (OR = 3.50, P = 9.2 x 10(-23) and OR = 3.39, P = 5.2 x 10(-82), respectively). GWAS loci explain 32% of disease risk in East Asians and 25% in Europeans, and correctly re-classify 20-37% of the cases in validation cohorts that are antibody-negative by the serum anti-PLA2R ELISA diagnostic test. Our findings highlight an unusual genetic architecture of MN, with four loci and their interactions accounting for nearly one-third of the disease risk.
Keywords: NF-KAPPA-B; GENOME-WIDE ASSOCIATION; SUSCEPTIBILITY LOCI; RISK ALLELES; DISEASE; ACTIVATION; RECEPTOR; MHC; METAANALYSIS; EXPRESSION